Cardiovocal syndrome due to a dilated pulmonary artery - Dina Moubayed; Trevor Lewis; Sami P. Moubayed; Annie Lapointe (Elsevier, 2019)
Cardiovocal syndrome, also known as Ortner's Syndrome, is a rare cause of unilateral vocal fold paralysis (UVFP) associated with cardiac failure. Typically, UVFP is left sided and related to compression or stretching of the left recurrent laryngeal nerve. The original clinical description relates UVFP to left atrium enlargement as heart failure progresses in the context of mitral stenosis. However, other cardiac abnormalities have since been described. Here we present the case of a 7-week old infant who initially came to the attention of pediatric cardiology due to failure to thrive in the context of a grade 4 systolic murmur. Laryngoscopy revealed UVFP on the left side. Echocardiography and MRI scanning confirmed atrial and ventricular septal defects and pulmonary artery dilatation as the likely cause of left recurrent laryngeal dysfunction. Keywords: Cardiovocal syndrome, Dilated, Pulmonary artery, Ortner's syndrome, Left recurrent laryngeal nerve